1993
DOI: 10.1128/iai.61.10.4302-4309.1993
|View full text |Cite
|
Sign up to set email alerts
|

Vitronectin binds to Pneumocystis carinii and mediates organism attachment to cultured lung epithelial cells

Abstract: Pneumocystis carinii attaches to alveolar epithelial cells during the development of pneumonia. Adhesive proteins found within the alveolar space have been proposed to mediate P. carinii adherence to lung cells. Vitronectin (Vn), a 75-kDa glycoprotein present in the lower respiratory tract, has substantial cell-adhesive properties and might participate in the host-parasite interaction during P. carinii pneumonia. To address whether Vn binds to P. carinii, we studied the interaction of radiolabeled Vn with puri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 37 publications
0
59
0
Order By: Relevance
“…Switching may be preprogrammed, particular MSG isoforms being expressed during certain environmental conditions or life-cycle stages (Cushion et al, 1988), or it may be induced by environmental differences encountered by the individual organisms. Even a population of P. c. carinii isolated from the same rat may be subjected to different environments within the animal, perhaps by interacting with any of a number of mammalian proteins known to bind MSG (Pottratz and Martin, 1990;Ezekowitz et al, 1991;Limper et al, 1993). Another possibility is that organisms may vary at random, in which case selection of organisms presenting a particular set of surface determinants could be a factor.…”
Section: Discussionmentioning
confidence: 99%
“…Switching may be preprogrammed, particular MSG isoforms being expressed during certain environmental conditions or life-cycle stages (Cushion et al, 1988), or it may be induced by environmental differences encountered by the individual organisms. Even a population of P. c. carinii isolated from the same rat may be subjected to different environments within the animal, perhaps by interacting with any of a number of mammalian proteins known to bind MSG (Pottratz and Martin, 1990;Ezekowitz et al, 1991;Limper et al, 1993). Another possibility is that organisms may vary at random, in which case selection of organisms presenting a particular set of surface determinants could be a factor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that IL-6 induces production of extracellular matrix proteins from epithelial cells [25]. In addition, other studies have demonstrated that PC attachment to alveolar epithelial cells is primarily mediated by the extracellular matrix proteins Fn [5] and Vn [7]. To determine the effects of IL-6 on A549 cell production of Fn and Vn, A549 cells were incubated in the presence of IL-6 (0-100 ng mL -1 ) for 24 h and levels of both Fn and Vn were quantified in the supernatants.…”
Section: Figurementioning
confidence: 99%
“…Ultrastructural studies have demonstrated close apposition and interdigitation between the outer membrane of PC trophozoites and the cell membrane of type I alveolar epithelial cells [3][4]. Previous studies have demonstrated the importance of the extracellular matrix proteins fibronectin (Fn) and vitronectin (Vn) as mediators of PC attachment to lung epithelial cells in vitro [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies using the human epithelial alveolar cell line A549 (with type II pneumocyte-like properties) have demonstrated that whole P. carinii organisms attach to A549 cells [15,15,16,16]. Binding is mediated by at least two adhesive glycoproteins, ¢bronectin and vitronectin, that bind to both P. carinii and A549 cells, and, thereby, are presumed to facilitate attachment to alveolar epithelium [16,17]. Further, MSG has been identi¢ed as a ¢bronectin binding protein required for P. carinii attachment [18].…”
Section: Role Of Msg In Organism Attachmentmentioning
confidence: 99%